Effects of the Oat Hay Feeding Method and Compound Probiotic Supplementation on the Growth, Antioxidant Capacity, Immunity, and Rumen Bacteria Community of Dairy Calves - Yong-Qing Guo; Ya-Ru Hu; Su-Ran Liu; Meng Wang; Zhen-Yu Xian; De-Wu Liu; Bao-Li Sun; Yao-Kun Li; Guang-Bin Liu; Ming Deng; Wen-Feng Hu; Qing-Shen Liu (MDPI AG, 2023)
This study aimed to investigate the effects of the oat hay feeding method and compound probiotics (CMP) on the growth, health, serum antioxidant and immune indicators, rumen fermentation, and bacteria community of dairy calves from 3 to 5 months of age. Forty-eight female Holstein calves (80 ± 7 days of age, 93.71 ± 5.33 kg BW) were selected and randomly divided into four groups. A 2 × 2 factorial design was adopted for the experiment, with the factors of the oat hay feeding method (fed as free-choice or 16.7% in the diet) and compound probiotics (CMP) inclusion (0.15% or 0%) in the pelleted starter. The results showed that, compared with giving oat hay as free-choice, feeding a diet of 16.7% oat hay increased the pelleted starter intake at 1-84 d (p < 0.05), with an average daily gain (ADG) at 61-84 d (p = 0.02); adding CMP to the pelleted starter did not significantly affect body weight, and reduced the fecal index (p < 0.05). Feeding 16.7% oat hay increased the concentration of IgA, IgG, and IgM (p < 0.01), while adding CMP increased the catalase (p < 0.01) and decreased the concentration of malondialdehyde (p < 0.01) in serum. Feeding 16.7% oat hay increased the ruminal concentration of propionic acid (p < 0.05) and isobutyric acid (p = 0.08), and decreased the ruminal pH (p = 0.08), the concentration of acetic acid (p < 0.05), and the ratio of acetic acid to propionic acid (p < 0.01). Feeding 16.7% oat hay reduced the relative abundance of ruminal Firmicutes, Unidentified-Bacteria, Actinobacteria, Prevotella, NK4A214-group, Olsenella, and Actinobacteriota (p < 0.05); adding CMP increased the relative abundance of ruminal Prevotella, Rikenellaceae-RC9-gut-group, Ruminococcus, NK4A214-group, and Ruminococcus (p < 0.05), and decreased the abundance of Desulfobacterora, Prevotella-7, and Erysipelotricaceae-UCG-002 (p < 0.05). In conclusion, feeding a diet of 16.7% oat hay increased the pelleted starter intake and average daily gain, while slightly reducing the ruminal pH values; adding CMP to the pelleted starter resulted in reduced diarrhea incidence, increased serum antioxidant capacity and immunity, as well as ruminal richness and diversity of microorganisms in dairy calves from 3 to 5 months of age.